High‐Performance Broadband Photodetectors of Heterogeneous 2D Inorganic Molecular Sb2O3/Monolayer MoS2 Crystals Grown via Chemical Vapor Deposition. Issue 17 (25th May 2020) - Ye, Kun; Liu, Lixuan; Huang, Junquan; Nie, Anmin; Zhai, Kun; Wang, Bochong; Wen, Fusheng; Mu, Congpu; Zhao, Zhisheng; Gong, Yongji; Xiang, Jianyong; Tian, Yongjun; et al.
Abstract: The newly emerged 2D materials heterostructures, including layered and nonlayered structures, are regarded as the building blocks for future high performance optoelectronic devices. However, it still remains a great challenge to directly synthesize 2D heterostructures for realizing broadband detection in photodetectors. In this work, the growth of vertically stacked inorganic molecular Sb2 O3 /monolayer MoS2 heterostructures through a two‐step chemical vapor deposition method is demonstrated, and high performance ultraviolet/near‐infrared photodetectors based on the achieved heterostructures are further developed. Excellent responsivity of 5.3 × 10 4 A W −1 and detectivity of 2.0 × 10 15 Jones are obtained under 457 nm illumination. Additionally, the photodetection range can be extended to near‐infrared region. Maximum responsivity of 7.8 A W −1, detectivity of 3.4 × 10 11 Jones, and fast response speed (<60 ms) are obtained under 1064 nm laser illumination at room temperature, which is far superior to those of the previously reported ultra‐thin 2D van de Waals heterostructures. The inorganic molecular Sb2 O3 /monolayer MoS2 heterostructures enrich the family of 2D materials heterostructures, showing potential applications in high performance functional electronics and optoelectronics. Abstract : Broadband and fast hybrid photodetectors are constructed based on the vertically stacked heterostructures of inorganic molecular crystal Sb2 O3 /monolayer MoS2 grown by a two‐step chemical vapor deposition method. A remarkably high responsivity and detectivity is achieved via optimizing the coverage ratio of Sb2 O3 atop the channel of monolayer MoS2 .